Coastal barriers from Argentina: Buenos Aires, Patagonia and Tierra del Fuego - Isla, Federico Ignacio (Quaternary and Environmental Geosciences, 2017)
Barriers, barrier islands and spits characterise low-lying coasts. However, they can grow along erosive coasts where there is a constant supply of sand, gravel, or both. At the Argentine coast, sandy barriers characterise the template coast of Buenos Aires. The availability of gravel at the Patagonian and Tierra del Fuego coasts induces the formation beach-ridge plains that can derived into coarse-grained spits. The morphology of these spits obeys to the basin depth and the availability of sediment. Recurved spits signify that the beach drift is locally modified by the action of waves or sediment-supply shortages. Some spits are today subject to local erosion (cannibalisation) that compensates these sediment deficits. Barriers and spits are ideal to locate harbours, marinas or touristic (resort) villages. However, the freshwater volumes inside their bodies are limited, even in areas where rain-fed aquifers have plenty of capacity. In this sense, resort villages are limited in their urban sprawl and planners should foresee these resource-based limitations.